Magnetic cell separation - Zborowski, M. (Maciej); Chalmers, J. J. (Jeffrey J.) (Laboratory techniques in biochemistry and molecular biology ;, 2008)
Cell separation is at the core of current methods in experimental biology and medicine. Its importance is illustrated by the large number of physical and biochemical principles that have been evaluated for application to cell separation. The development of cell separation methods is driven by the needs of biological and medical research, and the ever increasing demands for sensitivity, selectivity, yield, timeliness and economy of the process. The interdisciplinary nature of research in this area and the volume of information available in research publications and conferences necessitates a a basic description of the fundamental processes involved in magnetic cell separation that may help the user in navigating this wealth of information available online and in scientific publications. This book will appeal to researchers in many areas utilizing this technique including those working in cell biology, clinical research, inorganic chemistry, biochemistry, chemical engineering, materials science, physics and electrical engineering. Provides examples of how to calculate the volume magnetic susceptibility, a fundamental quantity for calculating the magnetic force acting on a cell, from various types of magnetic susceptibilities available in literature. Introduces the elements of magnetostatics as they apply to cell magnetization and the magnetization of magnetic micro- and nano- particles used for cell separation. Describes the parameters used to determine cell magnetophoresis.